Citrus Longhorned Beetle, Anoplophora chinensis (Forster) (Insecta: Coleoptera: Cerambycidae) - Jamba Gyeltshen; Amanda Hodges (EDIS, 2005)
The citrus longhorned beetle (CLHB), Anoplophora chinenis (Forster), is a serious pest of citrus in China but did not occur in the U.S. until it was detected in a Washington nursery in 2001. An eradication program was immediately implemented in Washington and there have subsequently been no new infestation reports (Anonymous 2005). However, with the increasing global trade and movement of plant materials, there is an imminent risk of establishment of CLHB in new areas. This document is EENY-357, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2005.